Waveguide polarizer with three irises for antennas of satellite television systems - Булашенко, Андрій Васильович; Пільтяй, Степан Іванович; Кушнір, Ганна Сергіївна; Булашенко, Олександр Васильович (Science-based technologies, 2021)
Frequency resources of satellite, terrestrial and other communication systems are expensive and limited. Modern telecommunication satellite systems use signals with two orthogonal linear or circular polarizations. Such signals allow the reuse of the same frequency band. In this case, the information capacity of the wireless channel is doubled. Circularly polarized signals reduce fading and destructive signal interference caused by multipath. For multipath propagation of electromagnetic waves, the use of signals with orthogonal circular polarization improves the performance of satellite systems. In antenna systems that use such signals, there is no need for precise angular orientation between the transmitting and receiving antennas. This pattern is used in mobile satellite telecommunication systems, where it is not possible to fix the orientation of one antenna relative to another. The listed features allow using antennas with polarization processing in modern wireless satellite television systems. Thus, an important engineering problem is the development and optimization of the characteristics of new waveguide polarizers for satellite antenna feeds. The results of the development and optimization of a new waveguide polarizer with irises for satellite television systems are presented in the article. The design of the developed polarizer consists of a square waveguide with three irises. Optimization of such a polarizer in the Ku-frequency range from 10.7 GHz to 12.8 GHz has been performed. The developed waveguide polarizer provides a differential phase shift of 90° ± 4.0°, a voltage standing wave ratio less than 2.03, an axial ratio less than 0.61 dB, and the crosspolar discrimination higher than 29.0 dB. Therefore, the created new polarizer based on a square waveguide with three irises ensures effective operation in the entire satellite Ku-band 10.7–12.8 GHz